The bureaucratisation of dissent - Harbisher, Benjamin (2016)
This thesis aims to examine the question of dissent, in relation to the tenuous position offered to campaigners in modern British society. Using figures such as George Hegel, Max Weber, and Michel Foucault, the work builds on a number of ideas that have remained central to the theory of political organisation, to illustrate how the British state has historically sought to control protests and manipulate public opinion. Themes to be examined within the thesis will include the articulation of common and individual rights (as they set the context for political disputes, and are often used to deny campaigner's the opportunity to participate in the policymaking process); the bureaucratic regulation and surveillance of demonstrators (through which, unsolicited public actions are now considered illegal); and the situation of activists within governmental discourses on terrorism (in which protestors are depicted as posing a threat to National Security). The main hypothesis is that in the UK, dissent has become the focus for an increasing number of agencies and administrative practices, through which it is intended that public demonstrations will eventually be constrained to follow a legitimate, staged, and thus an entirely manageable course of actions. This thesis also serves to address a gap in the developing field of surveillance studies, in which a number of key authors have failed to engage with the critical role that surveillance now plays in the suppression of dissent- with a particular emphasis being placed on how numerous causes and campaign groups are now monitored by the state and by private sector interests alike. Undeniably, the field of authority exerted over campaigners today is vast, and the strict management of public order affairs imposed by the police, enables an abundance of disciplinary techniques to take place, both prior to and during all protest events. Indeed, according to Foucault's theories on power, governmentality, and biopolitics, these legitimising mechanisms and procedures of coercion include visible forms of surveillance (the presence of the authorities during demonstrations); the overt surveillance and covert infiltration of campaign groups by the state and from private industry; and bureaucratic forms of surveillance enacted through a requirement to submit evidence of Health and Safety compliance, and Public Liability Insurance. Original empirical evidence supporting this thesis includes; Acts of Parliament covering seven-hundred years of legislation; Freedom of Information requests from three large-scale environmental campaigns; public order and counter-terrorism initiatives issued by HM Government; tactical policing manifestos; public inquiries into the misuse of police powers; and the newfound discourses that have been disseminated into the public domain concerning extremism. Putting it simply, the modern campaigner's lot is an unhappy one, in which activists must navigate an unconscionable array of legislative acts and have become the continual focus for corporate and state surveillance. Seemingly then, today's model of dissent offers two explicit choices, either conform to a wholly sanitised and regulated course of actions, or suffer the consequences.